People's Republic of China : 2019 Article IV Consultation-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for China. (IMF Staff Country Reports; Country Report ;, 2019)
After the slowdown in 2018, reflecting financial regulatory strengthening and softening external demand, growth stabilized in early 2019. Financial deleveraging and reduced interconnectedness between banks and non-banks have helped contain the build-up of financial risks, but vulnerabilities remain elevated and progress on rebalancing is mixed. While a moderate slowdown is expected in 2019, uncertainty around trade tensions remains high and risks are tilted to the downside.